Phase change material: Optimizing the thermal properties and thermal conductivity of myristic acid/palmitic acid eutectic mixture with acid-based surfactants - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Silakhori M.; Nur H. (2023)
In this study the addition of surfactant to fatty acids as phase change materials (PCMs) for solar thermal applications is proposed. The incorporation of surfactant additives into a eutectic mixture of fatty acids can significantly increase the value of latent heat storage and can suppress undercooling. We report the preparation of myristic acid/palmitic acid (MA/PA) eutectic mixture as Phase Change Material (PCM) with addition of 0, 5, 10, 15, and 20% sodium myristate (SM), sodium palmitate (SP), and sodium stearate (SS), the influence of surfactant additives on thermal properties and thermal conductivity of eutectic mixtures. It was found that the addition of 5% SM, 5% SP, and 5% SS to MA/PA eutectic mixture is very effective in depressing the liquid/solid phase change temperature, reducing the undercooling and increasing the amount of latent heat of fusion as well as thermal conductivity of eutectic PCM compared to eutectic PCM without surfactants. Furthermore MA/PA + 5%SS has the highest latent heat of fusion of 191.85 J g-1, while MA/PA + 5%SM showed the least undercooling of 0.34 C and the highest thermal conductivity of 0.242 W m-1 K-1. 2013 Elsevier B.V. All rights reserved.